Perilaku Kepemimpinan dan Penghargaan Terhadap Kepuasan Kerja Perawat di Rumah Sakit Umum Daerah (RSUD) Kota Mataram - Atfal, Bustanul; Sismulyanto, Sismulyanto; Menap, Menap (STIKES Yayasan RS.Dr.Soetomo, 2025)
The success key of health services in hospitals is intrinsically linked to various factors associated with nursing services. In this context, an anticipated increase in employee job satisfaction is expected to enhance performance, thereby facilitating the delivery of satisfactory service. Nurse job satisfaction is a critical determinant of nursing productivity. This study explored the relationship between leadership behavior and recognition concerning the job satisfaction of non-civil servant nurses at the Mataram City Regional General Hospital (RSUD). Employing a quantitative descriptive methodology with a cross-sectional design, the study involved a sample of 125 non-civil servant nurses. The data collected were primary, sourced from a questionnaire, and analyzed descriptively using the Chi-square test. The findings revealed a significance value of 0.000 (p < 0.005) for the leadership behavior variable (X1) about job satisfaction (Y), indicating acceptance of H1, as the X2 count exceeded the X2 table (12.767 > 9.488). The contingency coefficient calculation yielded a value of 0.30, suggesting a low correlation between job satisfaction and leadership behavior. For the reward variable (X2) to job satisfaction (Y), a significance value of 0.000 (p < 0.05) was obtained, confirming the acceptance of H1, as the X2 count surpassed the X2 table (44.079 > 9.488). The contingency coefficient calculation produced a value of 0.50, indicating a moderate relationship between rewards and job satisfaction among non-civil servant nurses. In conclusion, the data analysis suggests that both leadership behavior and rewards positively influence the job satisfaction of non-civil servant nurses.